Hepatites virais em usuários de drogas injetáveis (UDI) e 2007 usuários de cocaína não injetável (UCNI): fatores associados passíveis de estratégias preventivas - Keli Bahia Felicissimo Zocratto (2007)
The present study aimed to estimate factors which may be correlated to infections and coinfections of HIV and viral hepatitis types A, B and C among injecting and non-injecting drug users (IDUs and NIDUs respectively). This includes both awareness and behavioral factors. Three different databases were used. Two databases contained data about Brazilian IDUs for the time span 1998 and 2000-2001 (in the Project Ajude-Brasil I and the Project Ajude-Brasil II, respectively). The third database consisted of NIDU individuals living in Montevideo (Uruguay) and Buenos Aires (Argentina), during 2002-2003. A total of 793Brazilian IDUs (272 from the Project Ajude-Brasil I and 521 from the Project Ajude-Brasil II) and 824 NIDUs (480 from Buenos Aires and 344 from Montevideo) were involved in this study. For both groups, HCV infection was strongly associated to variables related to drug use, which suggests parenteral transmission of the virus among IDUs. At the same time, nonprotected sexual practice was associated with HBV and HIV infections in NIDUs and IDUs respectively. Awareness of the three types of viral hepatitis was strongly related to level of education, skin color, estimated time of drug use, the IDU being inserted in areas of mediumprevalence of HCV and the individuals awareness of his/her HIV serologic status. Needle and syringe sharing practices and the serologic status of the IDU were closely related to the individuals knowledge of HCV. Seronegative and HCV monoinfected subjects showed similar level of awareness of the virus. Since interactions within each social network may determine the choice of participants, these pathogens can be controlled by implementing public policies which would take into account peculiarities inherent in these groups specifically.